Neuroprotective Effects of Gagam-Sipjeondaebo-Tang, a Novel Herbal Formula, against MPTP-Induced Parkinsonian Mice and MPP+-Induced Cell Death in SH-SY5Y Cells. (4th December 2018) - Ko, Jade Heejae; Lee, Ju-Hee; Choi, Bobin; Park, Ju-Yeon; Kwon, Young-Won; Jeon, Songhee; Park, Sun-Dong; Kim, Seung-Nam
Abstract : Parkinson's disease is a neurodegenerative disease characterized by progressive cell death of dopaminergic neuron and following neurological disorders. Gagam-Sipjeondaebo-Tang (GST) is a novel herbal formula made of twelve medicinal herbs derived from Sipjeondaebo-Tang, which has been broadly used in a traditional herbal medicine. In the present study, we investigated the effects of GST against 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-induced motor abnormalities in mice and 1-methyl-4-phenylpyridinium (MPP + )-induced neurotoxicity in SH-SY5Y cell. First, we found that GST alleviated motor dysfunction induced by MPTP, and the result showed dopaminergic neurons recovery in substantia nigra. In the cell experiment, pretreatment with GST increased the cell viability and attenuated apoptotic cell death in MPP + -treated SH-SY5Y cells. GST also inhibited reactive oxygen species production and restored the mitochondrial membrane potential loss, which were induced by MPP + . Furthermore, GST extract significantly activated ERK and Akt, cell survival-related proteins, in SH-SY5Y cells. The effect of GST preventing mitochondrial dysfunction was antagonized by pretreatment of PD98059 and LY294002, selective inhibitors of ERK and Akt, respectively. Taken together, GST alleviated abnormal motor functions and recovered neuronal cell death, mitochondrial dysfunction, possibly via ERK and Akt activation. Therefore, we suggest that GST may be a candidate for the treatment and prevention of Parkinson's disease.